2017
DOI: 10.1016/j.cub.2017.10.019
|View full text |Cite
|
Sign up to set email alerts
|

Learning Biases Underlie “Universals” in Avian Vocal Sequencing

Abstract: Biological predispositions in vocal learning have been proposed to underlie commonalities in vocal sequences, including for speech and birdsong, but cultural propagation could also account for such commonalities [1-4]. Songbirds such as the zebra finch learn the sequencing of their acoustic elements ("syllables") during development [5-8]. Zebra finches are not constrained to learn a specific sequence of syllables, but significant consistencies in the positioning and sequencing of syllables have been observed b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
73
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 41 publications
(78 citation statements)
references
References 51 publications
(75 reference statements)
5
73
0
Order By: Relevance
“…Our results suggest that INs are learned from a tutor just like birds learn their song motifs from their 203 tutor. Previous studies have demonstrated the presence of biological predispositions in zebra finch song 204 learning [30,39]. For example, juvenile zebra finches that are individually tutored with random 205 sequences of syllables converge on similar motif sequences [30].…”
Section: Biological Predispositions In In Production and Learning 202mentioning
confidence: 99%
See 2 more Smart Citations
“…Our results suggest that INs are learned from a tutor just like birds learn their song motifs from their 203 tutor. Previous studies have demonstrated the presence of biological predispositions in zebra finch song 204 learning [30,39]. For example, juvenile zebra finches that are individually tutored with random 205 sequences of syllables converge on similar motif sequences [30].…”
Section: Biological Predispositions In In Production and Learning 202mentioning
confidence: 99%
“…Previous studies have demonstrated the presence of biological predispositions in zebra finch song 204 learning [30,39]. For example, juvenile zebra finches that are individually tutored with random 205 sequences of syllables converge on similar motif sequences [30]. To identify biological predispositions, 206 if any, in IN production, we experimentally tutored juvenile zebra finches with songs that lacked INs 207 ( Fig.…”
Section: Biological Predispositions In In Production and Learning 202mentioning
confidence: 99%
See 1 more Smart Citation
“…Another interactive hypothesis is that the structure in music results from long‐term distributed effects of multiple, individually varying minds that together create a kind of structural compromise that is pleasing to and learnable by all . These contrasting hypotheses have an exact parallel in the human language and animal communication literatures . In the nativist scenario, if all individuals share strongly constraining biases, music would emerge as a result of strengthening few, human‐wide tendencies toward musicality (akin to a vote by consensus).…”
Section: Introductionmentioning
confidence: 99%
“…17,18 These contrasting hypotheses have an exact parallel in the human language and animal communication literatures. [30][31][32][33] In the nativist scenario, if all individuals share strongly constraining biases, music would emerge as a result of strengthening few, human-wide tendencies toward musicality (akin to a vote by consensus). In the alternative interactive scenario, if all individuals have weak and potentially variable biases, music would emerge as a result of the interplay among individual-specific tendencies toward musicality, amplifying or averaging each other out (similarly to mixing paint of different colors).…”
Section: Introductionmentioning
confidence: 99%